Carcass pH and temperature changes due to factors related to bovine transport prior to slaughter - García-Ávila, George Alexander (2021)
The objective of this research was to elucidate the transport-related factors that influence the pH and temperature of the post-mortem muscle, in the carcass of the slaughtered animals in the Nobol slaughterhouse (GAI) in the province of Guayas, Ecuador. 605 cattle were sampled; the independent variables such as a mixture of categories, types of categories, sex, travel time and bedding type used for transportation were evaluated as possible causes of variations in pH and temperature. It was identified that the temperature of bovines subjected to more than 3 hours of travel and beds based on cane residue generate an increase in body temperature, affecting the quality of the meat and producing pale, soft and exudative meats (PSE); corroborating that transport-related factors are precursors of stress in livestock. Keywords: cows; slaughterhouse; PSE; DFD; mobility